2000
DOI: 10.1128/jvi.74.3.1200-1208.2000
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the trans -Activation Properties of Equine Herpesvirus 1 EICP0 Protein

Abstract: The EICP0 protein of equine herpesvirus 1 (EHV-1) is an early, viral regulatory protein that independently trans-activates EHV-1 immediate-early (IE), early, ␥1 late, and ␥2 late promoters. To assess whether this powerful trans-activator functions in conjunction with three other EHV-1 regulatory proteins to activate expression of the various classes of viral promoters, transient cotransfection assays were performed in which effector plasmids expressing the EICP22, EICP27, and IE proteins were used either singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 47 publications
2
43
0
Order By: Relevance
“…7B). Consistent with our previous findings (3,32), the wild-type IE protein activated expression of the IR5 promoter approximately 3.2-fold alone and 12.2-fold in combination with the auxiliary proteins over basal levels (pIR5-CAT alone). Expression of pIR5-CAT was not observed in the presence of the IE⌬407-757 mutant, which lacks the TFIIB-binding domain.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…7B). Consistent with our previous findings (3,32), the wild-type IE protein activated expression of the IR5 promoter approximately 3.2-fold alone and 12.2-fold in combination with the auxiliary proteins over basal levels (pIR5-CAT alone). Expression of pIR5-CAT was not observed in the presence of the IE⌬407-757 mutant, which lacks the TFIIB-binding domain.…”
Section: Resultssupporting
confidence: 79%
“…The EHV-1 IE gene (i) is located within each invertedrepeat region and encodes a polypeptide of 1,487 amino acids (aa) with a predicted molecular mass of approximately 155 kDa (19,21,27), (ii) has a product with a high degree of homology with HSV-1 ICP4 and the varicella-zoster virus ORF62 gene products (21), and (iii) is transcribed as a 6.0-kb spliced mRNA (19,27,51) that gives rise to both structurally and antigenically related protein species ranging from 125 to 200 kDa (7,8,51). In transient-cotransfection assays, the IE protein is a bifunctional regulatory protein capable of (i) negatively autoregulating its own promoter (55), (ii) independently activating EHV-1 early and heterologous viral promoters (55, 56), (iii) cooperating synergistically with two early auxiliary regulatory proteins (EICP22 and EICP27) to activate EHV-1 early and ␥1 late promoters (32,44,55,57,64), and (iv) acting antagonistically with a third early major regulatory protein, EICP0, to selectively repress expression of certain promoters from all classes of EHV-1 promoters, including ␥2 late promoters (3,35).Sequence alignment of the EHV-1 IE protein and other homologs in the subfamily Alphaherpesvirinae defined five colinear regions that harbor specific functional domains. Region 1 contains an acidic transactivation domain (TAD; aa 3 to 89) (58) and a serine-rich tract (SRT; aa 181 to 220).…”
mentioning
confidence: 99%
“…Our previous studies showed that the EICP0 protein interacts directly with basal transcription factors TFIIB and TBP as well as the IE protein (35) and contains a cysteine-rich zinc RING finger near the N terminus that is essential for activation of the E and L promoters (3). Of the many possibilities that may explain how NREBP abolishes the EICP0 protein's transactivation of its own promoter, one possible mechanism is that NREBP abolished the EICP0 protein's trans-activation by blocking or squelching its interaction with TFIIB and TBP.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in our laboratory showed that the EICP0 protein is a powerful trans-activator that activates all classes of EHV-1 promoters (3,4,34). To determine whether the EICP0 protein trans-activates the EICP0 promoter, the pEICP0-CAT reporter plasmid was used for transient transfection assays.…”
Section: Eicp0 Protein Very Weakly Trans-activates Its Own Promotermentioning
confidence: 99%
See 1 more Smart Citation